First report on pollutant accumulation and associated microbial communities in the freshwater sponge Spongilla lacustris (Linnaeus, 1759) from the sub-Arctic Pasvik River (Norway) - Lo Giudice, Angelina; Papale, Maria; Rizzo, Carmen; Giannarelli, Stefania; Caruso, Gabriella; Aspholm, Paul Eric; Maimone, Giovanna; Azzaro, Maurizio (Water Environment Research, 2024)
This explorative study was aimed at first characterizing the sponge Spongilla lacustris (Linnaeus, 1759) from the sub-Arctic Pasvik River (Northern Fennoscandia), in terms of associated microbial communities and pollutant accumulation. Persistent organic pollutants were determined in sponge mesohyl tissues, along with the estimation of the microbial enzymatic activity rates, prokaryotic abundance and morphometric traits, and the analysis of the taxonomic bacterial diversity by next-generation sequencing techniques. The main bacterial groups associated with S. lacustris were Alphaproteobacteria and Gammaproteobacteria, followed by Chloroflexi and Acidobacteria. The structure of the S. lacustris-associated bacterial communities was in sharp contrast to those of the bacterioplankton, being statistically close to those found in sediments. Dieldrin was measured at higher concentrations in the sponge tissues (3.1 +/- 0.4 ng/g) compared to sediment of the same site (0.04 +/- 0.03 ng/g). Some taxonomic groups were possibly related to the occurrence of certain contaminants, as was the case of Patescibacteria and dieldrin. Obtained results substantially contribute to the still scarce knowledge of bacterial community diversity, activities, and ecology in freshwater sponges.